How Peacekeepers Fight: Assessing Combat Effectiveness in United Nations Peace Operations. (1st January 2023) - Williams, Paul D.
Abstract: Contrary to popular perceptions, United Nations (UN) peacekeepers engage in combat fairly frequently. A central challenge facing the UN is thus calibration between force and politics: ensuring the organization's combat power is harnessed to viable political strategies for peace. However, the epistemic community on peacekeeping remains deeply divided between skeptics and proponents of "robust" operations, where peacekeepers are expected to use force to implement mission mandates. This article suggests that militarily effective, robust peacekeeping is most important for improving civilian protection and ensuring mission credibility in theaters where there is no peace to keep; proposes a novel framework and typology to assess combat effectiveness in UN peace operations; and compiles descriptive statistics for the 1948–2020 period. Finally, case studies of four battles involving UN peacekeepers in the Democratic Republic of the Congo illuminate the conditions that are conducive to the UN's combat effectiveness.